Protection Order Use Among Latina Survivors of Intimate Partner Violence. (July 2017) - Messing, Jill Theresa; Vega, Sujey; Durfee, Alesha
This mixed-methods study examines the impact of immigration status on the ability of Latina survivors of intimate partner violence (IPV) to file for and obtain a domestic violence protection order. Undocumented Latinas living in shelters are less likely to know what a protection order is or how to obtain one. At the same time, undocumented Latinas are more likely to believe that their partner would follow an order and that police would arrest their partner for a violation. Latina survivors of IPV live at the nexus of multiple systems of oppression; therefore, understanding their experiences using an intersectional framework is critically important.